Análisis propositivo del noticiario verdad al aire de radio la voz del santuario 89.3 fm y su incidencia en el comportamiento ético de los habitantes del barrio Las Pitas de la ciudad de Loja. Periodo noviembre 2014 - abril 2015. Propuesta alternativa - Vasquez Jimbo, Victor Fabian (2015)
This research was directed to consult the criterion of part of the listening public of the city of Loja, on the news program that emits Radio La Voz del Santuario, first issue, Monday through Friday. In the development of the subject methods, materials, techniques and instruments that contributed to clarify the research work was used. With the results obtained through the methodology, more precisely in the implementation of the survey and interviews were checked both general and specific objective to demonstrate the expectations outlined in the research and thus provide conclusions and recommendations of the research product. With all the fieldwork, an alternative proposal was made by analyzing the restructuring process of the news Truth Air. Fundamentally the support of the local residents Las Pitas city of Loja and relevant authorities on the subject, provided the necessary elements for building up the research process. Once known, analyzed and synthesized the problem the creation of the communication project for the restructuring of informative Truth to Air the same as this supported by proper use of technical and sound resources is proposed, but mostly serious, dynamic news team clear, objective, participatory, orderly, research, professional, able to lead and drive responsibly news; achieve the level of attention and acceptance from the audience, to recover this way trust and empathy between listeners and program. Keywords: Benefits, Barrio Las Pitas, Ethics, Truth Noticiario Air, Restructuring.